Dechlorination and para-hydroxylation of polychlorinated phenols by Rhodococcus chlorophenolicus. - Apajalahti, J H (1987)
In this paper we show that a polychlorophenol degrader Rhodococcus chlorophenolicus PCP-I initially attacked polychlorinated phenols (pentachlorophenol, 2,3,4,5-, 2,3,4,6-, and 2,3,5,6-tetrachlorophenol, and 2,3,5- and 2,3,6-trichlorophenol) by tetra- or trichlorohydroquinone-producing para-hydroxylation. The novel hydroxyl group was set in position 4, whether or not a substrate had chlorine substituent in this position. The hydroxyl was in each case derived from water molecules, as was shown by following the incorporation of oxygen from H2(18)O into the reaction products. Nevertheless, the para-hydroxylation reaction required the presence of molecular oxygen, whereas further metabolism of the reaction product, tetrachlorohydroquinone, proceeded also in anaerobiosis. All polychlorinated phenols were readily transformed at 41 degrees C, but none were transformed at 44 degrees C. In contrast to this, tetrachlorohydroquinone was metabolized at a high rate at 50 degrees C, but was not metabolized at 55 degrees C. Polychlorinated phenols were specific inducers of the para-hydroxylating enzymes; para-hydroxylated reaction products did not induce these enzymes. On the other hand, the degradation of tri- and tetrachlorohydroquinone was induced by any of the chlorophenols and also by hydroquinones.